The passengers' satisfaction with public bus service among middle-income users in Greater Cairo - Aref, Mohamed Nady (AUC Knowledge Fountain, 2019)
Public transport is an essential demand to ensure ease mobility for all the citizens to fulfill different life activities such as work, education and health. Passengers, around the world, search for a convenient bus service responds to their needs such as coverage, regular time table service, safety, facilities within terminals, better atmosphere inside the vehicle during the trip, and affordable fare. However, these basic needs are deteriorated on many countries due to lack of efficiency and responsiveness of the service operators. The aim of this study is to understand the most critical factors that influence on the passengers’ satisfaction with the public bus service in Egypt from the perspective of middle-income users specifically in both Cairo and Giza governorates. A qualitative study had been conducted in three main bus Terminals located in Tahrir, Boulak El Dakror and Lebanon Square in Cairo and Giza governorates. A sample of 40 passenger has been chosen based on different set of criteria include age, reliance of the service and monthly income. The analysis identifies the five categories that are essential for passengers of the public bus service. The first category is the facilities within the bus terminal which include secured waiting areas, bathrooms, cleanliness, lighting and personal security. The second category is the conditions of the vehicle that include design, drivers' behavior and information during the trip. The third category is the bus fare and to what extent passengers can afford to the bus service in Greater Cairo. The fourth one is the accurate time table that organizes the service during different working hours. The final category is the additional options for the passengers to improve the mobility and reduce stress during long trips. To improve the service, the operators have to include the passengers' perceptions and opinions on the evaluation process as the passengers represent the backbone of the bus service and interact directly with the service weaknesses.